Volumetric real-time particle-based representation of large unstructured tetrahedral polygon meshes - Voglreiter, Philip; Steinberger, Markus; Schmalstieg, Dieter; Kainz, Bernhard (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2012)
In this paper we propose a particle-based volume rendering approach for unstructured, three-dimensional, tetrahedral polygon meshes. We stochastically generate millions of particles per second and project them on the screen in real-time. In contrast to previous rendering techniques of tetrahedral volume meshes, our method does not need a prior depth sorting of geometry. Instead, the rendered image is generated by choosing particles closest to the camera. Furthermore, we use spatial superimposing. Each pixel is constructed from multiple subpixels. This approach not only increases projection accuracy, but allows also a combination of subpixels into one superpixel that creates the well-known translucency effect of volume rendering. We show that our method is fast enough for the visualization of unstructured three-dimensional grids with hard real-time constraints and that it scales well for a high number of particles. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2021-08-17
Keywords: GPU accelerated; mesh representations; particle-based; volume rendering